Synthesis and crystal chemical evolution of fresnoite powders - Wong, Chui L. (2013)
(Ba,Sr)2TiSi2O8 fresnoite powders were prepared via a Pechini process in which citric acid and ethylene glycol were used as complexing agents. The resulting gel contained a homogeneous distribution of the metal ions that suppressed the formation of (Ba,Sr)TiO3 perovskite as a secondary phase during calcination. Phase development was examined as by isochronal and isothermal reaction analysis. A combination of thermo- and differential gravimetric analysis (TGA–DGA), quantitative X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) confirmed that calcination at 900 °C/12 h yielded finely crystalline (∼70 nm) Ba2TiSi2O8 (BTS) and Sr2TiSi2O8 (STS). The endmembers and compositional intermediates crystallized directly from the Pechini resin and indirectly through reaction of (Ba,Sr)CO3, (Ba,Sr)TiO3 and a silica-rich glass intermediates. This new method for preparing fresnoite yields materials suitable for consolidation as dense monolithic dielectrics or for use as high surface area catalytic powders.